Incubation Period of Severe Acute Respiratory Syndrome Novel Coronavirus 2 that Causes Coronavirus Disease 2019: A Systematic Review and Meta-Analysis - Gizachew Tadesse Wassie, MPH; Abebaw Gedef Azene, MSc; Getasew Mulat Bantie, MPH; Getenet Dessie, MSc; Abiba Mihret Aragaw, MSc (Elsevier, 2020)
ABSTRACT: Background: Coronavirus disease 2019 (COVID-19) has currently become a major global public health problem. The prevalence of COVID-19 has increased rapidly worldwide. Because there is no effective COVID-19 vaccine available yet, it is increasingly important to understand the average incubation period of severe acute respiratory syndrome novel coronavirus 2 (SARS-CoV-2), the virus that causes COVID-19, to design appropriate preventive and control strategies. Objective: This systematic review and meta-analysis was designed to estimate the pooled average incubation period of SARS-CoV-2, the virus that causes COVID-19. Methods: We conducted a systematic electronic web-based search of online databases, including PubMed, Google Scholar, Embase, and the World Health Organization Hinari portal. We included peer-reviewed research studies written in the English language on the incubation period of SARS-CoV-2 using pre-defined quality and inclusion criteria. STATA version 15 statistical software was used to analyze the data. Joanna Briggs Institute critical appraisal quality assessment tool for observational studies was utilized to evaluate the included studies. We extracted relevant data and presented in a tabular form. The I2 test was used to assess heterogeneity across studies. Funnel plot asymmetry and Egger tests were used to check for publication bias. The final effect size was determined by applying a random-effects model. Results: Our search identified 206 studies, amongst which 18 studies, representing 22,595 participants were included in the final analysis. The pooled average incubation period of SARS-CoV-2 was 5.7 days (95% CI, 5.1-6.4). Subgroup analyses by geographic location showed that the pooled average incubation period of SARS-CoV-2 was 6.1 days (95% CI, 5.34-6.94) in China and 4.54 (95% CI, 3.9-5.2) in other countries (Singapore, South Korea, and globally). Conclusions: The pooled average incubation period of SARS-CoV-2 was about 6 days. The longest incubation period was observed in China. Global health initiatives as well as local health planners should consider this average incubation period when designing optimal prevention and control strategies for SARS-CoV-2. (Curr Ther Res Clin Exp. 2020; 81:XXX-XXX)